Ultrasound-guided platelet-rich plasma injection for distal biceps tendinopathy - Barker, Scott L (Shoulder Elbow, 2015)
BACKGROUND: Distal biceps tendinopathy is an uncommon cause of elbow pain. The optimum treatment for cases refractory to conservative treatment is unclear. Platelet-rich plasma has been used successfully for other tendinopathies around the elbow. METHODS: Six patients with clinical and radiological evidence of distal biceps tendinopathy underwent ultrasound-guided platelet-rich plasma (PRP) injection. Clinical examination findings, visual analogue score (VAS) for pain and Mayo Elbow Performance scores were recorded. RESULTS: The Mayo Elbow Performance Score improved from 68.3 (range 65 to 85) (fair function) to 95 (range 85 to 100) (excellent function). The VAS at rest improved from a mean of 2.25 (range 2 to 5) pre-injection to 0. The VAS with movement improved from a mean of 7.25 (range 5 to 8) pre-injection to 1.3 (range 0 to 2). No complications were noted. DISCUSSION: Ultrasound-guided PRP injection appears to be a safe and effective treatment for recalcitrant cases of distal biceps tendinopathy. Further investigation with a randomized controlled trial is needed to fully assess its efficacy.